European stone fruit yellows (ESFY) and its vector (Cacopsylla pruni, Scopoli) presence in Borsod-Abaúj-Zemplén County - Bodnár , Dominika; Tarcali, Gábor (GEORGIKON FOR AGRICULTURE, 2017)
European stone fruit yellows is one of the most serious diseases of peaches, cherries, sour cherries and in addition to apricots. The pathogen causing the disease now known as ’Ca. Phytoplasma prunorum’. The disease was diagnosed first time in 1992 in Hungary. During the spread of the disease it has reached Borsod-Abaúj-Zemplén County as well. Since the release, it became generally widespread and seriously threatens the growing of susceptible plants, especially of apricot. In 2009 and 2010 in Borsod-Abaúj-Zemplén County more stone plantation was carried out tests to determine the extent of the infestation. The majority of stocks evaluated severe infection have been identified that were confirmed by laboratory tests. During the tests, samples from 28 different stone fruit plant (apricots, peaches, cherries, sour cherries, wild plum / Prunus cerasifera /) were analyzed, of which 13 proved phytoplasma infected in the laboratory tests. From the time of the tests were carried out in 2009, the rate of destruction due to ESFY in the apricot trees of the region of Boldogkőváralja amounted to 70–80% to the year 2014. In 2014 the samples from a three years old apricot tree, derived from the settlement also gave positive results in the PCR test, to which varieties was ’Gönci kajszi’. Previously samples from such a young apricot tree has not been detected phyatoplasma infection. Vector of the ESFY, the plum psylla (Cacopsylla pruni) was observed during the examination of possible swarming routes, and 41 individuals were collected to search phytoplasma infection in 2016 in region of Boldogkőváralja. The ’Ca. Phytoplasma prunorum’ can be said to be widespread in the stone fruit orchards of Borsod-Abaúj-Zemplén County, and the disease means serious hazards to the stone fruits, especially the cultivation of apricots.